Southwest Airlines flight 1248 (B) - Diermeier, Daniel; Heinze, Justin (London : SAGE Publications Ltd, 2017)
After the companys first aviation fatality, Southwest Airliness CEO is faced with new and difficult decisions. The alacrity and compassion that characterized the companys response serves as a paradigm for any organization facing a future crisis situation.
Originally published: Diermeier, D., & Heinze, J. (2007). Southwest Airlines flight 1248 (B). 5-107-001(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Southwest Airlines Co. -- Case studies; Aircraft industry -- United States -- Case studies; Airlines -- Management -- Case studies